The Bidirectional Total Synthesis of Sampsonione P and Hyperibone I1. Issue 46 (20th September 2013) - Lindermayr, Katharina; Plietker, Bernd
<x xml:space="preserve">Abstract</x> Make it simple: The separation of framework‐decorating from framework‐constructing steps facilitated the selective introduction of one prenyl group next to allyl groups. The selective epoxidation of the more electron‐rich prenyl group led to the efficient formation of the tetrahydrofuran moiety in the title compounds. Spectroscopic analysis of hyperibone I and comparison with literature data led to a revision of the original structure.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>